Diagnostic aspects in surgical treatment of Fallot-type DORV (differential diagnosis) - Karimov, O. Kh.; Siromaha, S. O.; Dziuriy, I. V.; Abralov, Kh. K.; Lazorishinetz, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
In the article, in respect of the comparative aspect, there are considered data of non-invasive general clinical diagnostic methods, as well as angiography in patients with adjacent heart defects as tetralogy of Fallot and double outlet right ventricle (Fallot-type). 196 patients with Fallot-type DORV were included in the first group and 124 patients with tetralogy of Fallot – in the second comparative group. The results of general clinical diagnostic methods had descriptive form. The gold standard for differential diagnosis is the echocardiographic study, which, when using the original method, showed the high reliability of differential diagnosis of Fallot-type DORV.